Optimal child-related transfers and personal income tax with endogenous fertility - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2015)
To compare the systems of child benefits and of family tax deductions, we create a model with endogenous fertility and basic income, also financed from proportional wage taxes. Pensioners are neglected but younger and older workers are distinguished: the former raise children and receive child benefits, while the latter not. In such a model, the current average fertility depends on past average fertility, making the model dynamic. In our preferred parameter set, the deduction's efficiency is presumably lower than the benefit's and may even be lower than that of pure basic income.
Keywords: J13; 330; progressive income tax; child benefits; family tax deductions; endogenous fertility